Between Policy Idealism and Coastal Reality: A Qualitative Portrait of the Cities Without Slums Program Implementation in Lappa Village - Almasyah Pratama; Lukman Dahlan (Universitas Negeri Makassar, 2026)
This study evaluates the implementation and sustainability prospects of the